Some Civil Aspects of AI in Sport: New Challenges - Mateša, Blanka (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
Artificial intelligence (AI) is increasingly embedded in modern sport, shaping athlete performance analysis, injury prevention, refereeing, talent identification, and fan engagement. While AI-driven systems promise efficiency and competitive advantage, their deployment raises complex legal and ethical challenges, particularly regarding civil liability, data protection, transparency, and fairness. This paper examines the main applications of AI in sport and analyzes their legal implications under European Union law, with a particular focus on the General Data Protection Regulation (GDPR) and the EU Artificial Intelligence Act (AI Act). Special attention is devoted to liability for damage caused by AI errors in sport, including bodily injury, economic loss, and non-material harm. The research yielded results that sport constitutes a high-risk environment for AI use and demonstrated the need for special regulations for liability for damage caused by AI use and a governance framework that integrates legal regulation with ethical principles.